(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
The provision of financial services in the EU is characterized by the increased integration of the internal market, as well as, globalisation of said services. On the one hand, companies in the Member States can use the passport for the financial services, which allows their provision throughout the EU without the need to acquire a permit in each country separately. On the other hand, the financial crisis has shown a strong interdependence among financial markets globally and the negative effects deficiency in one of them can have on the EU market. Consequently, the possibilities for companies from non-member states to provide their services are limited in scope. However, gradually several possible methods of access were developed. Among them are setting up an EU subsidiary, operating a branch in the EU, or seeking a national exemption. One of the methods is determining the equivalence of third-country regulations and supervision mechanisms with the EU regime. This approach is sometimes deemed as controversial because the decision on equivalence is in the sole discretion of the European Commission, which causes fears that the process could be influenced by the political and economic necessities. The mechanism is characterized by the fragmentary approach – it is not prescribed in all acts on financial services and it is tailored to the needs of each act separately - and is granting fewer rights than a passport for financial services. Despite the controversy, its significance is reflected in the incentives for regulatory convergence with the EU regime and closer co-operation among regulatory bodies. This issue is proving to be more and more important, especially having in mind the newest developments in the EU market, as Brexit or new regime for the financial markets.